Evaluación técnica del cambio de la filosofía de control de la torre estabilizadora de crudo de Reficar mediante simulación para el mejoramiento de la calidad de los fluidos (2018)
The objective of this research is to apply a dynamic simulation in the Stabilizer Tower, in order to simulate a new control philosophy that allows to maintain the best quality conditions of the exit fluids when there are changes in the entrance flow to the tower. A general description of the refinery and the operation of the Stabilizing Tower is made, in order to understand the vapor stripping process that occurs. Then select certain theoretical values in order to model the process in a similar way to what happens in the Stabilizer Tower. Modeling the process, is ready to perform the dynamic simulation by proposing a procedure of analysis and control, in order that the process is carried out in the best way and to improve the quality of the fluids that are submitted to the process in the Stabilizer Tower. During the study the tuning of the controllers was determined and an optimum operating range to which the inlet flow of the Stabilizer tower can vary, which allows to obtain the naphtha and the LPG with the desired qualities. The simulation of the tower in a steady state is facilitated by Reficar S.A